Cystic benign prostatic hyperplasia in a dog - Tan, W. X.; Khor, Kuan Hua; Chan, S. M. (Veterinary Association Malaysia, 2015)
Old intact male dogs are often predisposed to benign prostatic hyperplasia. Both hypertrophy and hyperplasia of prostate gland occur due to hormonal influences. Clinical signs such as haematuria, stranguria and tenesmus are often associated with benign prostatic hyperplasia. A seven year-old local breed intact male dog was presented with a primary complaint of haematuria and stranguria. Diagnostic work-up conducted inclusive of complete blood count, serum biochemistry, urinalysis, abdominal radiograph, cystourethrography and abdominal ultrasonography. The dog was diagnosed with cystic benign prostatic hyperplasia. Prostatic omentalisation and castration were performed in this case.